Capacity to Provide Geriatric Specialty Care for Older Adults in Community Oncology Practices. (31st August 2020) - Williams, Grant R.; Weaver, Kathryn E.; Lesser, Glenn J.; Dressler, Emily; Winkfield, Karen M.; Neuman, Heather B.; Kazak, Anne E.; Carlos, Ruth; Gansauer, Lucy J.; Kamen, Charles S.; Unger, Joseph M.; Mohile, Supriya G.; et al.
Abstract: Background: American Society of Clinical Oncology guidelines recommend that patients ≥65 years of age starting chemotherapy undergo a geriatric assessment (GA) to inform and guide management; however, little is known about resources available in community oncology practices to implement these guidelines and to facilitate geriatric oncology research. Materials and Methods: Oncology practices within the National Cancer Institute Community Oncology Research Program (NCORP) were electronically surveyed in 2017 regarding the availability of specialty providers, supportive services, and practice characteristics, as part of a larger survey of cancer care delivery research capacity. Results: Of the 943 NCORP practices, 504 (54%) responded to the survey, representing 210 practice groups. The median new cancer cases per year ≥65 years of age was 457 (interquartile range 227–939). Of respondents, only 2.0% of practices had a fellowship‐trained geriatric oncologist on staff. Geriatricians were available for consultation or comanagement at 37% of sites, and of those, only 13% had availability within the oncology clinic (5% of overall). Practice size of ≥1, 000 new adult cancer cases (ages ≥18) per year was associated with higher odds (1.81, confidence interval 1.02–3.23) of geriatrician availability. Other multidisciplinary care professionals that could support GA were variably available onsite: social worker (84%), nurse navigator (81%), pharmacist (77%), dietician (71%), rehabilitative medicine (57%), psychologist (42%), and psychiatrist (37%). Conclusion: Only a third of community oncology practices have access to a geriatrician within their group and only 5% of community sites have access within the oncology clinic. Use of primarily self‐administered GA tools that direct referrals to available services may be an effective implementation strategy for guideline‐based care. Implications for Practice: Only a minority of community oncology practices in the U.S. have access to geriatric specialty care. Developing models of care that use patient‐reported measures and/or other geriatric screening tools to assess and guide interventions in older adults, rather than geriatric consultations, are likely the most practical methods to improve the care of this vulnerable population. Abstract : Treatment of cancer in older adults is complicated by the aging process. This article assesses the availability of geriatric specialty care to support the management of older adults with cancer in community oncology settings.